2018
DOI: 10.1002/ptr.6058
|View full text |Cite
|
Sign up to set email alerts
|

An Asparagus polysaccharide fraction inhibits MDSCs by inducing apoptosis through toll‐like receptor 4

Abstract: Despite decades of research, malignant tumors are extremely difficult to eliminate with conventional methods. Although surgical resection potentially eradicates the problem, only a few cases are suitable for operation, and other approaches often involve harmful consequences. Revolutionary methods are desperately needed to improve patient outcomes and diminish harmful side effects. Myeloid-derived suppressor cells (MDSCs), downregulators of the innate and adaptive immune systems, have been widely studied over t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Various effects of MDSCs on target cells have proven to be a critical pathogenic factor in SLE, including dysregulation of T helper type 17 (Th17) cells and differentiation of Treg (Ji et al 2016 ). MDSCs can also induce podocyte injury by increasing the levels of ROS in lupus nephritis (Zhang et al 2018a , b ). In conclusion, investigating the regulation of MDSCs may provide new insights into the therapy of SLE.…”
Section: Introductionmentioning
confidence: 99%
“…Various effects of MDSCs on target cells have proven to be a critical pathogenic factor in SLE, including dysregulation of T helper type 17 (Th17) cells and differentiation of Treg (Ji et al 2016 ). MDSCs can also induce podocyte injury by increasing the levels of ROS in lupus nephritis (Zhang et al 2018a , b ). In conclusion, investigating the regulation of MDSCs may provide new insights into the therapy of SLE.…”
Section: Introductionmentioning
confidence: 99%
“…In our current study, anti-proliferative effect of A. horridus on B-CPAP cells was observed and it was found that A. horridus extract with 101.24 μg/mL is required to reduce the B-CPAP cell proliferation by half. Based on the vast amount of cytotoxicity and anticancer studies, it has been confirmed that Asparagus species can be used as natural anticancer agent against various types of cancer [6,11,[26][27][28][29][30][31]. In the light of literature sources and our studies, it is concluded that methanol extract of A. horridus could be a potential anticancer agent for both liver and thyroid cancer treatments.…”
Section: Discussionmentioning
confidence: 58%
“…Wang Y is from Northwest University of Agriculture and Forestry Science and Technology, Li Y from the Dalian University of Technology, Li X from Nanjing University of Traditional Chinese Medicine. They mainly studied the mechanism of immunomodulation [15][16][17] and anti-inflammation [18][19][20] of traditional Chinese medicine. Keeping an eye on the three authors new articles will obtain an update on the immunological research of traditional Chinese medicine (TCM).…”
Section: Discussionmentioning
confidence: 99%